Volatility of the COVID-19 vaccine hesitancy: sentiment analysis conducted in Brazil - Celso Machado Júnior; Celso Machado Júnior; Daielly Melina Nassif Mantovani; Luísa Veras de Sandes-Guimarães; Maria do Carmo Romeiro; Cristiane Jaciara Furlaneto; Cristiane Jaciara Furlaneto; Roberto Bazanini (Frontiers in Public Health, 2023)
BackgroundVaccine hesitancy is a phenomenon that can interfere with the expansion of vaccination coverage and is positioned as one of the top 10 global health threats. Previous studies have explored factors that affect vaccine hesitancy, how it behaves in different locations, and the profile of individuals in which it is most present. However, few studies have analyzed the volatility of vaccine hesitancy.ObjectiveIdentify the volatility of vaccine hesitancy manifested in social media.MethodsTwitter’s academic application programming interface was used to retrieve all tweets in Brazilian Portuguese mentioning the COVID-19 vaccine in 3 months (October 2020, June 2021, and October 2021), retrieving 1,048,576 tweets. A sentiment analysis was performed using the Orange software with the lexicon Multilingual sentiment in Portuguese.ResultsThe feelings associated with vaccine hesitancy were volatile within 1 month, as well as throughout the vaccination process, being positioned as a resilient phenomenon. The themes that nurture vaccine hesitancy change dynamically and swiftly and are often associated with other topics that are also affecting society.ConclusionPeople that manifest the vaccine hesitancy present arguments that vary in a short period of time, what demand that government strategies to mitigate vaccine hesitancy effects be agile and counteract the expressed fear, by presenting scientific arguments.